Carbon Emission Potential Evaluation from China’s Airlines - Li, Long (Journal of Theory and Practice in Economics and Management, 2024)
The take-away business model is highly complex, and there is a lack of research on the issue of order allocation optimization in the existing literature. In view of the fact that this paper builds a take-out order allocation model based on the overall satisfaction of merchants and ordering customers, customer satisfaction is defined by the function of arrival time and ordering customer time, and an improved particle swarm optimization algorithm that can quickly and effectively solve the model is designed. The simulation experiment was carried out by using a region in Hexi District of Tianjin as an example to obtain the actual data, and the scientific validity of the model was verified.